Art as Document. Opening Historical Archive to Artistic Registers: Plan Barron 1938-2004 - Maria Rita Pais (Histories of Postwar Architecture)
Architecture research is traditionally addressed on perspectives aiming for object and author comprehension. We propose to change research point of view from creation to reception. Inspired by the revisitation of Maurice Merleau-Ponty’s (1960) idea of experience of art, we propose to gather, understand and discuss architecture throughout art production reading, and more specifically to understand obsolete military architecture complexity through artistic visions. This idea also follows Hans Robert Jauss Aesthetics of Reception (1964), including what happens in the consciousness received and in its aesthetic fruition. In the scope of the inhabitant spatial recognition, three researchers have been highlighted in recent years, with a perspective of relation with the work in architecture: Dana Arnold, (Arnold, 2014) presents methods of spatial investigation through biographies of the inhabitant, revealing personal meanings and strategies of relation with space; Jane Rendell with a work in understanding space through site-writing and site-specific as fictional forms of emotional relationship with the space; and Giuliana Bruno through the rescue of the "maps of the emotions" to make understandable some relations with space. Can we really represent, understand or make history about dissonant architecture through art reading? What can art production bring to history reading that matters in research? We don’t aspire to propose a new methodology, instead, we propose to present an ongoing curatorial experience to line up some methodological questions regarding the research on difficult heritage, that are not answered in traditional historical methodologies. More specifically, we propose to present and discuss how art can introduce more subjective but equally relevant layers of knowledge in the historical study of the object, especially when dealing with secret, codified or modified information and documentation, as it is the case of the Plan Barron of Defense of Lisbon and Setúbal Harbours.